ANALISIS PENGELOLAAN OBAT RUSAK, OBAT KADALUWARSA DAN OBAT DEAD STOCK DI PUSKESMAS WILAYAH KOTA PONTIANAK: ANALYSIS MANAGEMENT OF DAMAGED DRUGS, EXPIRED DRUG AND DEAD STOCK IN PUBLIC HEALTH CENTER IN PONTIANAK CITY - puspasari, heny; Weni Puspita (Akademi Farmasi Yarsi Pontianak, 2024)
Inefficient drug management can lead to budget overlap and inappropriate drug use. This results in a reduced availability of drugs, drugs accumulate due to inappropriate drug planning, and drug costs become expensive due to irrational use of drugs. Based on this, it shows that the percentage of damaged drugs, expired drugs, and dead stock drugs relatively high, so further research is needed on drug management. This study aims to describe and analyze the percentage of damaging drugs, expired drugs, and dead stock drugs in the UPTD of the Pontianak City Health Center. This study is a descriptive analysis with retrospective data collection by observing and evaluating data on damaged drugs, expired drugs, and dead stock drugs in 2020. The results showed no defective drugs were found in UPTD Puskesmas S and B, expired drugs in UPTD Puskesmas S and B. 15.4% and 16.7%, and dead stock in UPTD B was 3.3% and there was no dead stock in UPTD Puskesmas S. this study concluded that the percentage of damaged drugs was following the research indicators, namely 0%, the percentage Expired drugs and dead stock drugs are not following the research indicators, namely 0%, this is caused by several factors including changes in prescribing patterns and expiration dates that are too close, so it is necessary to evaluate drug planning according to to needs and improve management of expired drug management and stock is dead.